2020
DOI: 10.1111/tri.13690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐transplant sarcopenia on the estimation of standard liver volume in living‐donor liver transplant candidates: risk factor for post‐transplant small‐for‐size syndrome? A retrospective study

Abstract: The aim of the present study was to investigate whether LT candidates with sarcopenia are at an increased risk of receiving an inappropriate standard liver volume (SLV) estimation by standard body weight (BW)-derived SLV formula. Non-BW-SLV estimation formulas were tested in 262 LDLT donors and compared to a standard BW-SLV formula. The anthropometric parameters used were the thoracic width (TW-SLV) and thoracoabdominal circumference (TAC-SLV). Subsequently, sarcopenic and non-sarcopenic LDLT candidates (total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Pre‐LT sarcopenia is considered to be a factor that negatively affects the outcomes of treatment 11 . Sarcopenia has been found to be associated with reduced survival after LT and prolonged hospital stay 12,13 . However, there are few studies investigating the post‐transplantation effects of the presence of sarcopenia in pediatric patients before LT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre‐LT sarcopenia is considered to be a factor that negatively affects the outcomes of treatment 11 . Sarcopenia has been found to be associated with reduced survival after LT and prolonged hospital stay 12,13 . However, there are few studies investigating the post‐transplantation effects of the presence of sarcopenia in pediatric patients before LT.…”
Section: Introductionmentioning
confidence: 99%
“…11 Sarcopenia has been found to be associated with reduced survival after LT and prolonged hospital stay. 12,13 However, there are few studies investigating the post-transplantation F I G U R E 1 First, the L4/5 level was determined from sagittal reformatted images (A). Second, the psoas muscle area was measured from axial images (B) effects of the presence of sarcopenia in pediatric patients before LT.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies reported that sarcopenia was not related to short-term prognosis of LDLT patients [ 13 , 14 ]. It is possible that HAD with physical activity is more important than sarcopenia in terms of long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to prevent sarcopenia to potentially improve the overall treatment of patients undergoing LDLT [12]. However, previous studies have reported that sarcopenia is not related to prognosis of LDLT [13,14]. Therefore, the association between sarcopenia and prognosis in LDLT patients is still controversial and far from being elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…All the images were corrected layer by layer to obtain the accurate boundary of the lesion and the liver. In addition, SLV estimation was based on the formula in consideration of body surface area (BSA) 16 : SLV = 706.2 × BSA + 2.4, where BSA was calculated in consideration of height in centimeter and body weight (BW) in kilogram using the Dubois formula: BSA = 0.007184 × Height 0.725 × BW 0.4253 . Ultimately, the ratio of RLV to SLV (RLV/SLV) could be obtained.…”
Section: Methodsmentioning
confidence: 99%